The Tri-Center Education Ecosystem in the Era of Hyper-Disruption: A Collaborative Model Involving Family, School, and Community in Shaping Children’s Resilience and Digital Character - Ezalia Purnama Sari; Taufik Sakni; Qalka Sandi (Edumaspul: Jurnal Pendidikan, 2026)
The rapid digital disruption era presents unprecedented ethical and psychological challenges to children’s character development, necessitating a cohesive and synchronized approach from the Tri-Center of Education: family, school, and community. However, contemporary literature indicates that current multi-stakeholder collaborations remain highly fragmented and predominantly transactional, struggling to address the complexities of hyper-connectivity, algorithmic influences, and widening digital literacy gaps. To address this critical gap, this study employed a narrative literature review approach, systematically synthesizing peer-reviewed articles and institutional reports published between 2020 and 2025 sourced from the Google Scholar database. The thematic analysis reveals that overcoming these systemic barriers requires shifting from isolated, school-centric paradigms to integrated ecosystems that prioritize shared leadership, hybrid engagement, and culturally responsive practices. Consequently, this research proposes the "Phygital Tri-Center Synergy Model," an adaptive framework integrating relational infrastructure, collaborative capacity, and strategic technological integration. Ultimately, this model provides a practical roadmap for policymakers and educators to cultivate digital resilience and robust moral character in the 21st century.